LEAN APLICADO À GESTÃO DO PROCESSO DE PROJETO EM AMBIENTES DE SAÚDE UMA REVISÃO SISTEMÁTICA DE LITERATURA - Faria, Sheila; Hippert, Maria Aparecida Steinherz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Principles of the Lean philosophy can be presented as an efficient method to assist in the Project management process, particularly in health settings, which present many variables and multifaceted character. The article intends to report and bring the results found in the proposition of a Systematic Review of Literature, applied methodological process, in the search for studies that refer to the motivational questions of master's research in progress of the first author: "The contribution of the Lean methodology for the management complex of projects, especially in health contexts ". In this way, make a contribution to other researchers who want to use the method to establish a safe and reliable scientific basis.